Lifestyle Modification in Respiratory Tract Inflammation: Persian Medicine Perspective - Hanieh Tahermohammadi; Mahdi Hosseini; Mohammad Mahdi Bahrami; Mohammad Ali Tahermohammadi; Elham Ebrahimi; Narjes Mosavari; Ali Abdolahinia; Babak Daneshfard (Tehran University of Medical Sciences, 2024)
Excessive inflammation in the respiratory system could lead to life-threatening conditions. This situation is usually caused by irritants, allergens, pathogens, toxins, and pollutants, leading to airway inflammation. On the other hand, an inappropriate lifestyle can cause inflammation in different parts of the body including the respiratory tract. This study aimed to explore the recommended lifestyle modification for respiratory tract inflammation from the Persian medicine viewpoint in light of current evidence. In this review, first, we looked for lifestyle factors effective on the respiratory tract in Persian medicine sources. Then, PubMed, Web of Science, and Google Scholar were searched to find evidence about the mentioned factors, using the following keywords: psychological stress, sleep, food, exercise, gut, constipation, cold, and airway or respiratory tract. In line with Persian medicine, current literature confirms that psychological stress, intensive physical activity, allergic foods, and cold ambient trigger the beginning of the inflammation process in the respiratory system. It could happen through different pathways such as downregulation of Th1 cytokines expression, cold-inducible RNA binding protein (CIRP) synthesizing, mucin 5AC (MUC5AC) overexpression, activating transient receptor potential melastatin 8 (TRPM8) channels, inducing a neutrophilic type of inflammation and damaging the airway epithelium. Mild exercise, well-being of the gut microbiota status, and reduction of sleep duration have beneficial effects on the regression of inflammation. Lifestyle modification could play an important role in the prevention and treatment of respiratory tract inflammation. Future clinical investigations should be conducted to evaluate their effects.